Transformasi Pendidikan Di Era Digital dan Globalisasi: Integrasi AI, Digitalisasi Sistem, Kurikulum, dan Kesiapan SDM Pendidikan - Hilmi Sudarjat Barokah; Hajjah Alfi N; Arfianie Yuliantie (CV. PUSDIKRA MITRA JAYA, 2026)
The transformation of education in the digital and globalization era can no longer be understood merely as a change in the use of technology within classrooms. The transformation is far broader and more complex. Educational systems are now required to shift from conventional approaches toward learning ecosystems that are more adaptive, open, responsive, and data-driven. In this context, this article discusses the role of artificial intelligence (AI) in education, the digitalization of national education systems, curriculum transformation influenced by globalization, and the readiness of educational human resources in addressing the demands of the twenty-first century. This study employs a qualitative-descriptive literature review approach. The primary source of discussion was derived from group assignment documents, which were further developed through the synthesis of various concepts related to artificial intelligence in education, educational digitalization, twenty-first century competencies, and global education policies. The findings indicate that AI has considerable potential to support educational planning, particularly through data analysis, mapping student needs, predicting learning difficulties, and developing more personalized learning experiences. Nevertheless, the implementation of this technology is not always straightforward. In many schools, digitalization has improved the efficiency of educational governance, assessment systems, administration, and educational services. However, fundamental challenges remain, including limited internet connectivity, unequal access to digital devices, and the insufficient readiness of teachers and students to fully adapt to digital learning environments. Globalization also places additional pressures on educational systems. Curricula need to become more open to international standards, scientific developments, and the continuously changing demands of the labor market. At the same time, such openness must be carefully balanced so that local values, national identity, and the socio-cultural context of learners are not marginalized. Therefore, the readiness of teachers and educational personnel becomes a crucial determining factor. Technology should be positioned as a tool to strengthen the quality of learning rather than replacing the human role in guiding, evaluating, and shaping students’ character and moral development.